Screening for PRX mutations in a large Chinese Charcot-Marie-Tooth disease cohort and literature review - Xinran Ma; Xinran Ma; Xinran Ma; Xiaoxuan Liu; Xiaoxuan Liu; Xiaoxuan Liu; Xiaohui Duan; Dongsheng Fan; Dongsheng Fan; Dongsheng Fan (Frontiers in Neurology, 2023)
BackgroundPeriaxins (encoded by PRX) play an important role in the stabilization of peripheral nerve myelin. Mutations in PRX can lead to Charcot-Marie-Tooth disease type 4F (CMT4F).MethodsIn this study, we screened for PRX mutations using next-generation sequencing and whole-exome sequencing in a large Chinese CMT cohort consisting of 465 unrelated index patients and 650 healthy controls. Sanger sequencing was used for the validation of all identified variants. We also reviewed all previously reported PRX-related CMT cases and summarized the clinical manifestations and genetic features of PRX-related CMTs.ResultsThe hit rate for biallelic PRX variants in our cohort of Chinese CMT patients was 0.43% (2/465). One patient carried a previously unreported splice-site mutation (c.25_27 + 9del) compound heterozygous with a known nonsense variant. Compiling data on CMT4F cases and PRX variants from the medical literature confirmed that early-onset (95.2%), distal amyotrophy or weakness (94.0%), feet deformity (75.0%), sensory impairment or sensory ataxia (65.5%), delayed motor milestones (60.7%), and spinal deformity (59.5%) are typical features for CMT4F. Less frequent features were auditory impairments, respiratory symptoms, late onset, dysarthria or hoarseness, ophthalmic problems, and central nervous system involvement. The two cases with biallelic missense mutations have later onset age than those with nonsense or frameshift mutations. We did not note clear correlations between the type and site of mutations and clinical severity or distinct constellations of symptoms.ConclusionConsistent with observations in other countries and ethnic groups, PRX-related CMT is rare in China. The clinical spectrum is wider than previously anticipated.